2004
DOI: 10.1177/0310057x0403200310
|View full text |Cite
|
Sign up to set email alerts
|

Pethidine and Skin Warming to Prevent Shivering during Endovascular Cooling

Abstract: We tested the efficacy of pethidine and cutaneous warming to prevent shivering during percutaneous cooling in unanaesthetized patients. Ten patients scheduled for cranial neurosurgery received pethidine infusion and skin warming. The Setpoint™ internal heat-exchanging catheter was inserted and cooling to 33.5°C was started. Clonidine and chlorpromazine were given as “rescue medication” to treat shivering. General anaesthesia was planned to be induced after cooling was complete. Rewarming was initiated at dural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, whatever the reason, meperidine is one of the most effective antishivering drugs known and is frequently used for treatment of postoperative shivering (65). Nonetheless, meperidine alone is not usually sufficient for induction of therapeutic hypothermia (66).…”
Section: Opioidsmentioning
confidence: 99%
“…However, whatever the reason, meperidine is one of the most effective antishivering drugs known and is frequently used for treatment of postoperative shivering (65). Nonetheless, meperidine alone is not usually sufficient for induction of therapeutic hypothermia (66).…”
Section: Opioidsmentioning
confidence: 99%
“…They reported good feasibility with mild shivering in nine patients. Leslie and colleagues [ 36 ] reported that a combination of a low level of meperidine (target plasma level: 0.4 mg/ml) and skin warming in 10 patients scheduled for neurosurgery was insufficient to prevent shivering. However, study results have also shown a large range of meperidine levels (0.1 to 0.9 μg/ml) and therefore have to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…However, only in the study by Leslie and colleagues [ 36 ] were meperidine levels measured and sedation assessed with a validated scale; in none of the aforementioned studies was the interaction between meperidine and skin warming examined. In contrast, by means of an approach described by Slinker [ 29 ], our present volunteer study is able to demonstrate an additive interaction between meperidine and skin warming.…”
Section: Discussionmentioning
confidence: 99%
“…For example, meperidine was frequently used for the treatment of perioperative shiver because of its beneficial and characteristic therapeutic profile (Burks et al, 1980). The administration of opioids inhibits the motor (shiver) thermal response at twice the rate as the vasoconstrictive response, at any given dose (Leslie et al, 2004). The antishivering action of meperidine is already present at blood levels that do not lead to any observable respiratory depression or sedation, for example, a relatively small dose (25 mg, iv) of meperidine decreases the shivering threshold by 2°C (Alfonsi et al, 1998).…”
Section: Induction Of Therapeutic Hypothermiamentioning
confidence: 99%